Carbohydrate depletion in roots and leaves of salt-stressed potted Citrus clementina L. - Arbona, Vicent; Marco, Aureli J.; Iglesias, Domingo J.; Lopez-Climent, Maria F.; Talón, Manuel; Gómez-Cadenas, Aurelio (2017)
In citrus, damage produced by salinity is mostly due to toxic ion accumulation, since this salt-sensitive crop adjusts osmotically with high efficiency. In spite of this observation, the putative role of sugars as osmolites under salinity remains unknown. In this work, we have studied carbohydrate contents (total hexoses, sucrose and starch) in leaves and roots of citrus grown under increasing salinity. The experimental system was characterized through the analyses of several parameters known to be strongly affected by salinity in citrus, such as chloride accumulation, photosynthetic rate, ethylene production and leaf abscission. Three-year-old plants of the Clementina de Nules cultivar grafted on Carrizo citrange rootstock were watered with three different levels of salinity (NaCl was added to the watering solutions to achieve final concentrations of 30, 60 and 90 mM). Data indicate that salt stress caused an accumulation of chloride ions in a way proportional to the external increase in NaCl. The adverse conditions reduced CO2 assimilation, increased ethylene production and triggered abscission of the injured leaves. Data also show that salinity induced progressive depletions of carbohydrates in leaves and roots of citrus plants. This observation clearly indicates that sugar accumulation is not a main component of the osmotic adjustment machinery in citrus.